Christian Realism of Reinhold Niebuhr in the Multipolar Geopolitical Crisis of the Twenty-First Century - R. F. Bhanu Viktorahadi; Martha Gabriela Hernández (Kongregasi Hati Kudus Yesus (RSCJ) Indonesia, 2026)
This study analyzes Reinhold Niebuhr’s Christian Realism as a framework of political ethics for addressing the multipolar geopolitical crisis of the twenty-first century. The study emerges from the limitations of mainstream international relations theories, such as realism, liberalism, constructivism, and critical geopolitics, which have not adequately provided a normative foundation for responding to global conflicts, structural injustice, neoliberalism, and contemporary digital geopolitics. The study employs a qualitative approach based on library research and focuses on theological and hermeneutical analyses of Reinhold Niebuhr’s thought. The researcher collected data through documentation studies and academic literature reviews, while the analysis employed hermeneutical interpretation, interdisciplinary dialogue, and normative synthesis. The primary sources include Niebuhr’s major works, especially Moral Man and Immoral Society and The Nature and Destiny of Man, along with various scholarly works on political theology and contemporary geopolitics. The findings demonstrate that Christian Realism offers a framework of political ethics that realistically acknowledges human sin and egoism while maintaining a normative commitment to justice and moral responsibility in global politics. Christian Realism operates at epistemological, normative, and practical levels in interpreting multipolarity, international conflict, neoliberalism, and global digital domination. The implications of this study indicate that Christian Realism can function as an alternative framework of global political ethics capable of bridging political realism and moral values within the context of contemporary systemic chaos. The originality of this study lies in its effort to reconstruct Christian Realism as a framework of geopolitical ethics that responds contextually to multipolarity and digital geopolitics in the twenty-first century.